Aerosol processing technique for the synthesis of mixed-phase copper on carbon catalyst: insights into CO2 adsorption and photocatalytic activity. (3rd December 2022) - Subedi, Nabin; Mesceriakovas, Arunas; Pham, Khai; Heponiemi, Anne; Karhunen, Tommi; Saarinen, Jarkko J; Lassi, Ulla; Lähde, Anna
Abstract: In this study, spray pyrolysis; an aerosol processing technique was utilized to produce a mixed-phase copper on carbon (Cu/Cu x O@C) catalyst. The catalyst production was performed via chemical reduction of copper nitrate by a reducing sugar, i.e. glucose, using aqueous solution. The physical and chemical properties of the produced particles was assessed using various characterization techniques. The synthesis temperature had pronounced effect on the final particles. Since CO2 adsorption onto the catalyst is an important step in catalytic CO2 reduction processes, it was studied using thermogravimetric and temperature programmed desorption techniques. Additionally, photocatalytic activity of the particles was evaluated by gas-phase oxidation of acetylene gas which revealed excellent activity under both UV and visible light irradiation indicating the possible use of wider range of the solar spectrum.